Rhodium-Based Metal-Organic Polyhedra Assemblies for Selective CO2Photoreduction - Ghosh, Ashta C.; Legrand, Alexandre; Rajapaksha, Rémy; Craig, Gavin A.; Sassoye, Capucine; Balázs, Gabor; Farrusseng, David; Furukawa, Shuhei; Canivet, Jerome; Wisser, Florian M. (Journal of the American Chemical Society, 2022)
Heterogenization of molecular catalysts via their immobilization within extended structures often results in a lowering of their catalytic properties due to a change in their coordination sphere. Metal-organic polyhedra (MOP) are an emerging class of well-defined hybrid compounds with a high number of accessible metal sites organized around an inner cavity, making them appealing candidates for catalytic applications. Here, we demonstrate a design strategy that enhances the catalytic properties of dirhodium paddlewheels heterogenized within MOP (Rh-MOP) and their three-dimensional assembled supramolecular structures, which proved to be very efficient catalysts for the selective photochemical reduction of carbon dioxide to formic acid. Surprisingly, the catalytic activity per Rh atom is higher in the supramolecular structures than in its molecular sub-unit Rh-MOP or in the Rh-metal-organic framework (Rh-MOF) and yields turnover frequencies of up to 60 h-1and production rates of approx. 76 mmole formic acid per gram of the catalyst per hour, unprecedented in heterogeneous photocatalysis. The enhanced catalytic activity is investigated by X-ray photoelectron spectroscopy and electrochemical characterization, showing that self-assembly into supramolecular polymers increases the electron density on the active site, making the overall reaction thermodynamically more favorable. The catalyst can be recycled without loss of activity and with no change of its molecular structure as shown by pair distribution function analysis. These results demonstrate the high potential of MOP as catalysts for the photoreduction of CO2and open a new perspective for the electronic design of discrete molecular architectures with accessible metal sites for the production of solar fuels.
Created from Fastlane, Scopus look-up